THE IMPACT OF DIGITALISATION ON LOCAL CULTURAL PRESERVATION THROUGH EDUCATION: A LITERATURE REVIEW ON TECHNOLOGY-BASED LEARNING INNOVATIONS FOR STRENGTHENING LOCAL WISDOM VALUES IN THE ERA OF GLOBALISATION - Dedi Zulkarnain Pulungan; Hamni Damayanti (International Journal of Teaching and Learning, 2025)
Digital transformation has brought about major changes in various aspects of life, including education and culture. This study aims to analyse the impact of digitalisation on the preservation of local culture through education and to identify relevant technology-based learning innovations for strengthening local wisdom values in the era of globalisation. This study uses a literature review method. The results show that digitisation plays an important role in supporting the documentation, promotion, and revitalisation of local culture through interactive digital media such as videos, online platforms, augmented reality, and e-learning. However, if not balanced by cultural awareness and contextual education policies, digitisation also has the potential to cause cultural homogenisation and erosion of local values. Technology-based learning can be a strategic means of internalising local wisdom if it is designed with participatory, creative, and adaptive principles in line with the times. Thus, the synergy between technological innovation, the education system, and local wisdom values becomes the main foundation for preserving national identity amid the tide of digital globalisation